2021
DOI: 10.3390/app12010141
|View full text |Cite
|
Sign up to set email alerts
|

Copper Nanoparticles: Synthesis and Characterization, Physiology, Toxicity and Antimicrobial Applications

Abstract: Metallic nanoparticles are a new class of materials with applications in medicine, pharmaceutical and agriculture. Using biological, chemical and physical approaches, nanoparticles with amazing properties are obtained. Copper is one of the most-found elements and plays an important part in the normal functioning of organisms. Coper nanoparticles have superior antibacterial properties when comparing them to present day antibiotics. Moreover, apart from their antibacterial role, antifungal, antiviral and antican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 81 publications
0
51
0
1
Order By: Relevance
“…Since Cu NPs have a strong reduction ability, the redox cycles between Cu 0 , Cu 1+ , and Cu 2+ mediate the generation of reactive oxygen species; thus, inducing cell death [ 21 ]. Cu 2+ and Cu 1+ ions eluted from Cu NPs can be absorbed by bacteria, thus imparting damage to the cell membrane by solidifying protein structures or altering enzyme function, further leading to cell death [ 45 , 46 ]. It is also suggested that Cu 2+ ions can penetrate the cell membrane upon combining with the plasma membrane during electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Cu NPs have a strong reduction ability, the redox cycles between Cu 0 , Cu 1+ , and Cu 2+ mediate the generation of reactive oxygen species; thus, inducing cell death [ 21 ]. Cu 2+ and Cu 1+ ions eluted from Cu NPs can be absorbed by bacteria, thus imparting damage to the cell membrane by solidifying protein structures or altering enzyme function, further leading to cell death [ 45 , 46 ]. It is also suggested that Cu 2+ ions can penetrate the cell membrane upon combining with the plasma membrane during electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…It is also suggested that Cu 2+ ions can penetrate the cell membrane upon combining with the plasma membrane during electrostatic interactions. The cell wall of gram-negative bacteria, consists of anionic surfaces (lipopolysaccharide molecules) that have a high affinity to the positively charged Cu 2+ , thus leading to increased toxicity [ 46 ]. More so, nanoparticles become a focal source of ions upon contact with the bacteria cell, because the dissolution takes place in the localized area [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Thomas et al (2015) indicate a high potential in applying silver nanoparticles to urinary catheters for preventing catheter-associated infections, especially the attachment and colonization of bacteria [99,100]. The scientific literature also indicates that copper nanoparticles have antibacterial properties [101,102]. Therefore, it is important to evaluate phage-nanoparticle interactions due to data about the possibility of irreversible inactivation of phages (e.g., E. coli-specific) by nanoparticles [103,104].…”
Section: Discussionmentioning
confidence: 99%
“…The poisoning of cells' redox system, mitochondrial damage, as well as proteins and DNA injuries will kill the cells. 294,295 Besides the possibilities with nanocomposite PSAs in biomedical applications, there are some serious limitations that are mainly caused by the natural resources from which PSAs are originated, which degrades their pharmaceutical and biological applications. To name a few, batch-to-batch variations, the possibility of microbial contamination, viscosity drop during the storage stages, viscosity thickening, as well as uncontrolled rate of hydration can be addressed.…”
Section: Limitations and Challengesmentioning
confidence: 99%